Caracterização da educação na comunidade quilombola do Rio das Rãs no município de Bom Jesus da Lapa - TEIXEIRA, Manoel Messias (2016)
This work characterizes the education offered by the state to the Quilombo Community of the Frogs River in the city of Bom Jesus da Lapa with attention to their educational practices and their social effects, especially with regard to the customs and traditions and man maintenance field. This is a bibliographic study, documentary and field. He addressed the implemented political pedagogical project and the curriculum proposed by the Municipal Department of Education. There were several issues: the teaching strategies positively impact the assisted community? This educational process helps to alleviate the problems of the context of rural education? He tried to also check through field research is the pedagogical issues are addressed through a work process accompanying the school reality of rural education in municipal schools of the Community. families to questionnaires were applied (177 people) and professionals interviewed (24 people) active in education. There was a positive perception of the community with respect to the performance of schools in the attributes of identity and quilombo perpetuation, as well as in matters related to nature and environment. The left professional transpire an unsatisfactory perception regarding the education offered.